Perbedaan prevalensi obesitas dan berat badan lebih pada siswa sekolah menengah atas (SMA) negeri antara daerah urban dan rural di Kabupaten Gianyar - Made Windha Prajaskari Armi; I Made Pande Dwipayana (Universitas Udayana, 2018)
Obesity and overweight that occur in adolescence would be a high risk to increase in adulthood. The risk factors associated with obesity include residential areas and carbohydrate intake. This study aimed to compare the prevalence of obesity and overweight in public high school student between urban and rural areas in district Gianyar. This study is observational and cross sectional design. Sample was a public high school student in urban (SMAN 1 Gianyar) and rural (SMAN 1 Tegallalang) areas of district Gianyar. Measurement of height and weight respondents to calculate BMI and then BMI analyzed to obtain prevalence of obesity and overweight in each region. The prevalence of overweight was 12.2% (296 respondents) and obesity was 5.4%. The result of this study show that the prevalence of overweight and obesity in urban areas (14.2% and 7.4%) is higher than rural areas (10.1% and 3.4%), p value=0.067 (p>0.05). So, it can be said there is no statistically significant difference. It can be concluded that there is no difference in obesity and overweight prevalence in public high school student between urban and rural areas in district Gianyar. This result expected to be used as a reference of similar research or futher studies to find risk factors associated with obesity in urban and rural areas, especially in the districts Gianyar. Keywords: obesity, urban, rural.